2016
DOI: 10.1371/journal.pone.0167497
|View full text |Cite
|
Sign up to set email alerts
|

Remembered or Forgotten?—An EEG-Based Computational Prediction Approach

Abstract: Prediction of memory performance (remembered or forgotten) has various potential applications not only for knowledge learning but also for disease diagnosis. Recently, subsequent memory effects (SMEs)—the statistical differences in electroencephalography (EEG) signals before or during learning between subsequently remembered and forgotten events—have been found. This finding indicates that EEG signals convey the information relevant to memory performance. In this paper, based on SMEs we propose a computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…These differences are often apparent in amplitude or latency modulations of the ERP (Paller, Kutas, & Mayes, 1987;Paller, McCarthy, & Wood, 1988;Fukuda & Woodman, 2015) as well as distinct oscillations ranging from changes in the alpha, theta or gamma rhythms (Hanslmayr, Spitzer, & Bauml, 2009;Klimesch et al, 1996;Osipova et al, 2006;Staudigl & Hanslmayr, 2013). A few recent studies have also shown that single-trial EEG activity can predict subsequent memory by combining pre-stimulus and stimulus-locked activity during encoding, reaching similar decoding accuracies as in the present study (59.6%; Noh et al, 2013; see also Tan, Smitha, & Vinod, 2015;Sun, Qian, Chen, Wu, Luo, & Pan, 2016). However, in all of these studies, differences in encoding-related brain activity could be due to differences in the perceptual input (the same images tend to be remembered by the same people), differences in familiarity of the stimuli, distinct encoding strategies, or the attentional state of the observer at encoding (Klimesch, 2012;Dubé et al, 2013;Hanslmayr & Staudigl;.…”
Section: Discussionsupporting
confidence: 88%
“…These differences are often apparent in amplitude or latency modulations of the ERP (Paller, Kutas, & Mayes, 1987;Paller, McCarthy, & Wood, 1988;Fukuda & Woodman, 2015) as well as distinct oscillations ranging from changes in the alpha, theta or gamma rhythms (Hanslmayr, Spitzer, & Bauml, 2009;Klimesch et al, 1996;Osipova et al, 2006;Staudigl & Hanslmayr, 2013). A few recent studies have also shown that single-trial EEG activity can predict subsequent memory by combining pre-stimulus and stimulus-locked activity during encoding, reaching similar decoding accuracies as in the present study (59.6%; Noh et al, 2013; see also Tan, Smitha, & Vinod, 2015;Sun, Qian, Chen, Wu, Luo, & Pan, 2016). However, in all of these studies, differences in encoding-related brain activity could be due to differences in the perceptual input (the same images tend to be remembered by the same people), differences in familiarity of the stimuli, distinct encoding strategies, or the attentional state of the observer at encoding (Klimesch, 2012;Dubé et al, 2013;Hanslmayr & Staudigl;.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the idea that how a stimulus is initially processed is critical for memory performance, a large body of research has shown that neural activity patterns during encoding can predict subsequent memory (Sanquist et al, 1980;Wagner et al, 1998;Paller and Wagner, 2002;Daselaar et al, 2004; Kuhl et…”
Section: Introductionmentioning
confidence: 95%
“…A recent, prominent example of such an advance in machine learning is the application of convolutional neural networks (ConvNets), particularly in computer vision tasks. Thus, first studies have started to investigate the potential of ConvNets for brain‐signal decoding [Antoniades et al, ; Bashivan et al, ; Cecotti and Graser, ; Hajinoroozi et al, ; Lawhern et al, ; Liang et al, ; Manor et al, ; Manor and Geva, ; Page et al, ; Ren and Wu, ; Sakhavi et al, ; Shamwell et al, ; Stober, ; Stober et al, ; Sun et al, ; Tabar and Halici, ; Tang et al, ; Thodoroff et al, ; Wang et al, ] (see Supporting Information, Section A.1 for more details on these studies). Still, several important methodological questions on EEG analysis with ConvNets remain, as detailed below and addressed in this study.…”
Section: Introductionmentioning
confidence: 99%